Pengembangan Website untuk Mendorong Sustainable Tourism di Kampung Tarung, Sumba Barat - Radeswandri, Radeswandri; Ginting, Ginta (Milenial: Journal for Teachers and Learning, 2025)
Tourism has the potential to be a source of income and welfare of the community. Tarung Kampung in West Sumba, which still runs the trust of Merapu, has the potential as a leading tourist destination. Different from other remote traditional villages, Tarung Village is located in the City of Waikabubak, with architecture and typical spatial planning that is full of philosophy. Although promising, Tarung Village is still less well known than other traditional villages such as Panglipuran or Wae Rebo. This study is a research research and survey results on the potential to show unfavorable promotions even though this village has been listed on the government's official website. This study involved 80 Sumba community respondents. This study aims to develop sustainable tourism in Tarung Village. The results of the study include the development of websites for promotion of tourist areas so that it can make a real contribution in developing and promoting the tourist area